Realizing Majorana zero modes in superconductor-semiconductor heterostructures - Lutchyn, Roman; Bakkers, E. P. A. M.; Kouwenhoven, Leo; Krogstrup, Peter; Marcus, Charles; Oreg, Y. (Nat Rev Mater, 2017)
Realizing topological superconductivity and Majorana zero modes in the laboratory is one of the major goals in condensed matter physics. We review the current status of this rapidly-developing field, focusing on semiconductor-superconductor proposals for topological superconductivity. Material science progress and robust signatures of Majorana zero modes in recent experiments are discussed. After a brief introduction to the subject, we outline several next-generation experiments probing exotic properties of Majorana zero modes, including fusion rules and non-Abelian exchange statistics. Finally, we discuss prospects for implementing Majorana-based topological quantum computation in these systems.